(untitled) (Global Journal of Medical Research, 2025)
Antimicrobial peptides AMPs are bioactive molecules known for their strong antimicrobial properties against a variety of microorganisms The increasing prevalence of antibiotic-resistant infections coupled with a scarcity of newly developed antibiotics has intensified the search for novel sources of AMPs Plant-derived AMPs present several benefits compared to conventional antibiotics Consequently this research focused on screening various plant species to identify new antimicrobial peptides Water-soluble proteins were extracted from the dried plant materials using an aqueous extraction buffer The resulting extracts were evaluated for antibacterial activity with the minimum inhibitory concentration MIC being determined followed by separation through thin layer chromatography and subsequent agar overlay bioautography Protein extracts from five different plants exhibited antibacterial properties against both Gram-positive and Gram-negative bacteria with inhibition zones measuring between 11 and 22 mm The extract from Raphanus sativus demonstrated the most extensive antibacterial activity with inhibition zones ranging from 16 to 19 mm against Staphylococcus aureus ATCC 12493 Streptococcus epidermidis ATCC 12228 Escherichia coli NCTC 13846 and Acinetobacter baumannii ATCC 19606 The extract of Vitis labrusca showed inhibition zones of 18 mm and 11 mm against S aureus and S epidermidis respectively while Ricinus communis exhibited inhibition zones of 15 mm and 22 mm against the same bacteria Hibiscus sabdariffa extract displayed a smaller inhibition zone of 12 mm against Pseudomonas aeruginosa ATCC 27853